Optical laminate and its manufacturing method, smart window including the same, and automobile and building fittings using the same
By eliminating a separate base material and optimizing sealant regions, the laminate structure simplifies manufacturing, reduces thickness, and improves adhesion, addressing the inefficiencies of conventional optical laminates.
Patent Information
- Application Number
- JP2024539397
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2021-12-30
- Filing Date
- 2022-12-16
- Publication Date
- 2025-01-24
AI Technical Summary
Conventional variable transmittance optical laminates require a separate base material for forming a conductive layer, leading to complex manufacturing processes, increased thickness, and reduced transmittance, as well as poor interfacial adhesion of the sealant.
The laminate structure omits a separate base material by directly forming transparent conductive layers on polarizing plates, with specific regions for sealant application, enhancing adhesion and reducing thickness.
This simplifies the manufacturing process, reduces thickness, improves transmittance, and enhances interfacial adhesion of the sealant, resulting in a more efficient and cost-effective optical laminate.
Smart Images

Figure 2025501942000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to a variable transmittance optical laminate and a method for producing the same, a smart window including the same, and automobile and building fittings to which the same is applied. [Background technology]
[0002] In general, an external light blocking coating is often applied to glass windows of vehicles and other means of transportation. However, the glass windows of conventional means of transportation have a fixed transmittance, and the external light blocking coating also has a fixed transmittance. Therefore, the windows of such conventional means of transportation have a fixed overall transmittance, which may lead to accidents. For example, if the overall transmittance is set low, there is no problem during the day when there is sufficient light in the surroundings. However, in the case of nighttime when there is insufficient light in the surroundings, there is a problem that the driver, etc., has difficulty in properly checking the surroundings of the means of transportation. Alternatively, if the overall transmittance is set high, there is a problem that the driver, etc., may be dazzled during the day when there is sufficient light in the surroundings. For this reason, a variable transmittance optical laminate capable of changing the transmittance of light when a voltage is applied has been developed.
[0003] The variable transmittance optical stack is driven by applying a voltage to drive the liquid crystal to change the transmittance. The variable transmittance optical stack developed to date is manufactured by forming a conductive layer for driving the liquid crystal on a separate substrate and combining it with other elements such as a polarizer.
[0004] For example, Japanese Patent Application Laid-Open No. 2018-010035 also discloses a variable transmittance optical laminate including a transparent electrode layer formed on a polycarbonate (PC) substrate having a predetermined thickness.
[0005] However, when a separate substrate is used to form the conductive layer, the manufacturing process becomes complicated, which increases manufacturing costs, and the thickness of the laminate increases, resulting in a phase difference and causing a change in transmittance.
[0006] In addition, the sealant formed along the outer peripheral surface of the liquid crystal layer to seal the liquid crystal layer is formed on an alignment film for aligning the liquid crystal compound, which not only reduces the active area of the optical laminate but also reduces the interfacial adhesion of the sealant.
[0007] Therefore, there is a need to develop a variable transmittance optical stack that can simplify the manufacturing process of the optical stack, reduce the thickness, and improve the interfacial adhesion between the active region of the optical stack and the sealant. Summary of the Invention [Problem to be solved by the invention]
[0008] An object of the present invention is to provide a variable transmittance optical laminate that does not require a separate substrate for forming a conductive layer, and thus has a simplified manufacturing process.
[0009] Another object of the present invention is to provide a variable transmittance optical laminate that does not include a separate substrate for forming a conductive layer, thereby significantly reducing the thickness.
[0010] Another object of the present invention is to provide a variable transmittance optical laminate having improved transmittance in a transmission mode by not including a separate substrate for forming a conductive layer.
[0011] Another object of the present invention is to provide a variable transmittance optical laminate having an improved active area by adjusting the ratio of a sealant area formed on an alignment film.
[0012] Another object of the present invention is to provide a variable transmittance optical laminate in which the interfacial adhesion of the sealant is improved by adjusting the ratio of the sealant region formed on the alignment film.
[0013] Another object of the present invention is to provide a smart window including the variable transmittance optical laminate, and a fitting for an automobile or building to which the smart window is applied.
[0014] However, the problems to be solved by the present invention are not limited to those mentioned above, and other problems not mentioned will be clearly understood by those skilled in the art from the following description. [Means for solving the problem]
[0015] The present invention relates to a variable transmittance optical laminate including a first laminate having a first polarizing plate, a first transparent conductive layer, and a first alignment film stacked in this order; a second laminate facing the first laminate and having a second polarizing plate, a second transparent conductive layer, and a second alignment film stacked in this order; a liquid crystal layer disposed between the first laminate and the second laminate; and a sealant formed along an outer peripheral surface of the liquid crystal layer to seal the liquid crystal layer, wherein at least one of the first transparent conductive layer and the second transparent conductive layer is formed in direct contact with at least one of the first polarizing plate and the second polarizing plate, the sealant includes a first region overlapping at least one of the first alignment film and the second alignment film in a planar direction and a second region not overlapping, and the width of the first region is 5% to 70% of the sum of the widths of the first region and the second region.
[0016] In a first aspect of the present invention, the sealant region corresponding to the first region may be a sealant region formed on at least one of a first alignment film and a second alignment film, and the sealant region corresponding to the second region may be a sealant region that is not formed on the first alignment film or the second alignment film.
[0017] In the second aspect of the present invention, the sum of the width of the first region and the width of the second region may be a sealant width.
[0018] In the third aspect of the present invention, the width of the first region may be from 0.1 mm to 3.0 mm.
[0019] In a fourth aspect of the present invention, a crossed transmittance of the active region measured at an interface between the active region and the first region of the liquid crystal layer may be equal to or greater than 0% and less than 3.0%.
[0020] In a fifth aspect of the present invention, the peel strength of the sealant may be from 100 mN / 4 mm to 500 mN / 4 mm.
[0021] In a sixth aspect of the present invention, at least one of the first transparent conductive layer and the second transparent conductive layer may be formed in direct contact with either one of the first polarizing plate and the second polarizing plate without any separate substrate between them.
[0022] In a seventh aspect of the present invention, at least one of the first transparent conductive layer and the second transparent conductive layer may include an easy-adhesion layer between the transparent conductive layer and one of the first polarizing plate and the second polarizing plate, and may be formed in direct contact with the transparent conductive layer.
[0023] In an eighth aspect of the present invention, at least one of the first transparent conductive layer and the second transparent conductive layer may contain one or more materials selected from the group consisting of transparent conductive oxides, metals, carbon-based materials, conductive polymers, conductive inks, and nanowires.
[0024] In a ninth aspect of the present invention, at least one of the first polarizing plate and the second polarizing plate may include one or more functional layers selected from the group consisting of a protective layer, a phase difference adjusting layer, and a refractive index adjusting layer.
[0025] In a tenth aspect of the present invention, at least one of the first polarizing plate and the second polarizing plate may have a thickness of 30 to 200 μm.
[0026] In an eleventh aspect of the present invention, the liquid crystal layer may include one or more spacers selected from the group consisting of ball spacers and column spacers.
[0027] In a twelfth aspect of the present invention, the ball spacer may have a diameter of 1 to 10 μm.
[0028] In a thirteenth aspect of the present invention, an area of the ball spacer in the liquid crystal layer may be 0.01% to 10% of an area of the liquid crystal layer.
[0029] In a fourteenth aspect of the present invention, the variable transmittance optical laminate may further include one or more layers selected from the group consisting of an alignment film, an adhesive layer, an ultraviolet absorbing layer, and a hard coating layer.
[0030] The present invention also relates to a method for producing the variable transmittance optical laminate.
[0031] The present invention also relates to a smart window comprising the variable transmittance optical laminate.
[0032] The present invention also relates to an automobile in which the smart window is applied to at least one of a front window, a rear window, a side window, a sunroof window, and an interior partition.
[0033] The present invention also relates to a building fixture including the smart window. Effect of the Invention
[0034] In addition, according to the variable transmittance optical laminate of the present invention, it is possible to omit the steps of forming a conductive layer on a substrate and then bonding it to other components in order to form a conventional optical laminate, thereby simplifying the manufacturing process compared to conventional optical laminates.
[0035] In addition, according to the variable transmittance optical laminate of the present invention, a conductive layer is formed directly on one side of a polarizing plate, and a separate substrate for forming the conductive layer is not required, so that the thickness can be significantly reduced compared to conventional optical laminates.
[0036] In addition, according to the variable transmittance optical laminate of the present invention, a conductive layer is formed directly on one side of a polarizing plate, and a separate substrate for forming the conductive layer is not required, so that the transmittance in the light transmission mode can be improved compared to conventional optical laminates.
[0037] In addition, the variable transmittance optical stack according to the present invention can have an improved active area compared to conventional optical stacks by adjusting the ratio of the sealant region formed on the alignment film.
[0038] In addition, according to the variable transmittance optical laminate of the present invention, by adjusting the proportion of the sealant region formed on the alignment film, the interfacial adhesion of the sealant can be improved compared to conventional optical laminates. [Brief description of the drawings]
[0039] [Figure 1] FIG. 1 is a diagram showing a layered structure of a variable transmittance optical layered body according to an embodiment of the present invention. [Figure 2a] FIG. 2a is a diagram showing a laminate structure of a polarizing plate according to an embodiment of the present invention. [Figure 2b] FIG. 2b is a diagram showing a laminate structure of a polarizing plate according to an embodiment of the present invention. [Figure 2c] FIG. 2c is a diagram showing a laminate structure of a polarizing plate according to an embodiment of the present invention. [Figure 2d] FIG. 2d is a diagram showing a laminate structure of a polarizing plate according to an embodiment of the present invention. [Figure 2e] FIG. 2e is a diagram showing a laminate structure of a polarizing plate according to one embodiment of the present invention. [Diagram 3] FIG. 3 is a diagram showing a cross section of a laminated structure of a variable transmittance optical laminate according to an embodiment of the present invention. [Figure 4] FIG. 4 is a diagram showing the sealant and the alignment film of the variable transmittance optical laminate according to FIG. 3 superimposed in a planar direction. [Diagram 5] FIG. 5 is a diagram showing a layered structure of a variable transmittance optical layered body according to another embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0040] The variable transmittance optical laminate of the present invention has a technical feature that a transparent conductive layer for driving liquid crystal is directly formed on one side of a polarizing plate, so that a separate substrate for forming a conductive layer is not required, thereby reducing the thickness of the laminate and improving the transmittance in a light transmission mode. Also, the technical feature is that the interfacial adhesion between the active region of the optical laminate and the sealant is improved by adjusting the ratio of the sealant region formed on the alignment film.
[0041] More specifically, the present invention relates to a variable transmittance optical laminate including a first laminate having a first polarizing plate, a first transparent conductive layer, and a first alignment film stacked in this order; a second laminate facing the first laminate and having a second polarizing plate, a second transparent conductive layer, and a second alignment film stacked in this order; a liquid crystal layer disposed between the first laminate and the second laminate; and a sealant formed along the outer peripheral surface of the liquid crystal layer to seal the liquid crystal layer, wherein at least one of the first transparent conductive layer and the second transparent conductive layer is formed in direct contact with at least one of the first polarizing plate and the second polarizing plate, the sealant includes a first region overlapping in a planar direction with at least one of the first alignment film and the second alignment film and a second region not overlapping, and the width of the first region is 5% to 70% of the sum of the widths of the first region and the second region.
[0042] The variable transmittance optical laminate of the present invention is particularly suitable for technical fields in which light transmittance can be changed by applying a voltage, and can be used, for example, in smart windows.
[0043] The smart window of the present invention refers to an optical structure that controls the amount of light or heat passing through by changing the light transmittance according to the application of an electrical signal. That is, the smart window of the present invention is provided so that it can be changed to a transparent, opaque or translucent state according to a voltage, and includes, but is not limited to, variable transmittance glass, light control glass or smart glass.
[0044] The smart window can be used as a partition for dividing the interior space of a vehicle or building or for privacy protection, or as a light-gathering window placed in an opening of a building. It can also be used as a highway sign, bulletin board, scoreboard, clock or advertising screen, and can be used to replace glass in vehicles such as windows or sunroofs of automobiles, buses, airplanes, ships or trains.
[0045] The variable transmittance optical laminate of the present invention can be used as a smart window in the various technical fields described above, but since the conductive layer is directly formed on the polarizing plate, a separate substrate for forming the conductive layer is not required, and therefore the thickness is thin and the bending characteristics are advantageous, and the variable transmittance optical laminate of the present invention can be particularly preferably used as a smart window for vehicles or buildings. In one or more embodiments, the smart window to which the variable transmittance optical laminate of the present invention is applied can be used as a front window, rear window, side window, and sunroof window of an automobile, or a building fixture, and can be used not only for blocking external light, but also for dividing the interior space of an automobile or building, such as an interior partition, or for privacy protection.
[0046] Hereinafter, the embodiments of the present invention will be described in more detail with reference to the drawings. However, the following drawings attached to this specification are only illustrative of preferred embodiments of the present invention and serve to further understand the technical concept of the present invention together with the above-mentioned content of the invention, and therefore the present invention should not be interpreted as being limited only to the matters shown in these drawings.
[0047] The terms used in this specification are for the purpose of describing the embodiments and are not intended to limit the present invention. In this specification, the singular form includes the plural form unless otherwise specified in the text. For example, the term "polarizing plate" used in this specification may mean at least one polarizing plate among the first polarizing plate and the second polarizing plate, the term "transparent conductive layer" may mean at least one transparent conductive layer among the first transparent conductive layer and the second transparent conductive layer, and the term "alignment film" may mean at least one alignment film among the first alignment film and the second alignment film.
[0048] As used herein, the terms "comprises" and "comprising" are used in a sense that does not exclude the presence or addition of one or more other components, steps, operations and / or elements other than the stated components, steps, operations and / or elements. The same reference numerals refer to the same components throughout the specification.
[0049] Spatially relative terms such as "below," "bottom," "lower," "upper," "top," and the like, may be used to easily describe the relationship of one element or component to another element or component as depicted in the drawings. Spatially relative terms should be understood to include different orientations of elements in use or operation in addition to the orientation depicted in the drawings. For example, if an element depicted in the drawings is turned upside down, an element described as "below" or "below" another element may be placed "above" the other element. Thus, the exemplary term "below" can include both an orientation of below and above. Elements may be oriented in other directions, and thus the spatially relative terms may be interpreted accordingly.
[0050] As used herein, the "planar direction" may be interpreted as the direction perpendicular to the polarizers and / or transparent conductive layers, ie, the direction viewed from the user's viewing side.
[0051] Fig. 1 is a diagram showing a layered structure of a variable transmittance optical laminate according to one embodiment of the present invention, and Fig. 2 is a diagram showing a layered structure of a polarizing plate according to one or more embodiments of the present invention. Fig. 3 is a diagram showing a cross section of the layered structure of a variable transmittance optical laminate according to one embodiment of the present invention, and Fig. 4 is a diagram showing a sealant and an alignment film of the variable transmittance optical laminate according to Fig. 3 superimposed in a planar direction. Fig. 5 is a diagram showing a layered structure of a variable transmittance optical laminate according to another embodiment of the present invention.
[0052] Referring to FIG. 1, a variable transmittance optical stack according to one embodiment of the present invention may include a first polarizer 100-1, a second polarizer 100-2, a first transparent conductive layer 200-1, a second transparent conductive layer 200-2, and a liquid crystal layer 300.
[0053] Referring to FIG. 2, the polarizing plate 100 may include a polarizer 110 and may further include functional layers such as a protective layer 120, a phase difference control layer 130, and a refractive index control layer 140 on one or both sides of the polarizer 110. For example, the polarizing plate 100 may include a polarizer 110 and a protective layer 120 stacked on one or both sides of the polarizer 110 (see FIG. 2a and FIG. 2b). Alternatively, the polarizing plate 100 may include a polarizer 110, a protective layer 120 stacked on one side of the polarizer 110, and a phase difference control layer 130 stacked on the other side opposite to the one side of the polarizer 110 (see FIG. 2c). Alternatively, the polarizing plate 100 may include a polarizer 110, a protective layer 120 stacked on one side of the polarizer, and a phase difference control layer 130 and a refractive index control layer 140 stacked in order on the other side opposite to the one side of the polarizer 110 (see FIG. 2d). Alternatively, the polarizer 110 may include a protective layer 120 stacked on one surface of the polarizer, and a protective layer 120 and a phase difference adjusting layer 130 stacked in sequence on the other surface of the polarizer 110 opposite the one surface (see FIG. 2e).
[0054] The polarizer 110 may be a conventional or later developed polarizer, for example, a stretched type polarizer or a coated type polarizer.
[0055] In one embodiment, the stretched polarizer may include a stretched polyvinyl alcohol (PVA)-based resin. The polyvinyl alcohol (PVA)-based resin may be a polyvinyl alcohol-based resin obtained by saponifying a polyvinyl acetate-based resin. Examples of the polyvinyl acetate-based resin include polyvinyl acetate, which is a homopolymer of vinyl acetate, and copolymers of vinyl acetate and other monomers copolymerizable therewith. The other monomers may be unsaturated carboxylic acid-based, unsaturated sulfonic acid-based, olefin-based, vinyl ether-based, and acrylamide-based monomers having an ammonium group. The polyvinyl alcohol (PVA)-based resin may be modified, for example, polyvinyl formal or polyvinyl acetal modified with aldehydes.
[0056] In an embodiment, the coating type polarizer may be formed by a liquid crystal coating composition, and the liquid crystal coating composition may include a reactive liquid crystal compound and a dichroic dye.
[0057] The reactive liquid crystal compound may refer to a compound that includes, for example, a mesogen skeleton and includes one or more polymerizable functional groups. Such reactive liquid crystal compounds are variously known as reactive mesogens (RMs). The reactive liquid crystal compound can be polymerized by light or heat to form a cured film in which the liquid crystal alignment is maintained and a polymer network is formed.
[0058] The reactive liquid crystal compound may be a monofunctional or polyfunctional reactive liquid crystal compound. The monofunctional reactive liquid crystal compound is a compound having one polymerizable functional group, and the polyfunctional reactive liquid crystal compound is a compound having two or more polymerizable functional groups.
[0059] The dichroic dye is a component contained in the liquid crystal coating composition to impart polarization properties, and has a property that the absorbance in the long axis direction of the molecule is different from that in the short axis direction. The dichroic dye may be a dichroic dye that has been used or will be developed in the future, and may include at least one dye selected from the group consisting of azo dyes, anthraquinone dyes, perylene dyes, merocyanine dyes, azomethine dyes, phthaloperylene dyes, indigo dyes, dioxazine dyes, polythiophene dyes, and phenoxazine dyes.
[0060] The liquid crystal coating composition may further include a solvent capable of dissolving the reactive liquid crystal compound and the dichroic dye, for example, propylene glycol monomethyl ether acetate (PGMEA), methyl ethyl ketone (MEK), xylene, chloroform, etc. Also, the liquid crystal coating composition may further include a leveling agent, a polymerization initiator, etc. within a range that does not inhibit the polarization properties of the coating film.
[0061] The protective layer 120 serves to preserve the polarization characteristics of the polarizer 110 from post-processing and external environments, and may be implemented in the form of a protective film.
[0062] 2a and 2b, the protective layer 120 may be formed on one or both sides of the polarizer 110 in direct contact therewith, but is not limited thereto. For example, the protective layer may be used as a multi-layer structure in which one or more protective layers are continuously stacked, or may be formed in direct contact with other functional layers.
[0063] In one or more embodiments, the protective layer 120 may include one or more selected from the group consisting of polyethylene terephthalate (PET), polyethylene isophthalate (PEI), polyethylene naphthalate (PEN), polybutylene terephthalate (PBT), diacetyl cellulose (diacetyl cellulose), triacetyl cellulose (TAC), polycarbonate (PC), polyethylene (PE), polypropylene (PP), polymethyl acrylate (PMA), polymethyl methacrylate (PMMA), polyethyl acrylate (PEA), polyethyl methacrylate (PEMA), and cyclic olefin polymer (COP).
[0064] The retardation control layer 130 is for compensating for the optical properties of the optical laminate and may be implemented in the form of a retardation film, etc., and may be a conventional or later developed retardation film, etc. For example, a quarter wave plate (1 / 4 wave plate) or a half wave plate (1 / 2 wave plate) for delaying the phase of light may be used, and these may be used alone or in combination.
[0065] The phase difference adjusting layer 130 may be formed on one surface of the polarizer 110 in direct contact therewith, as shown in Fig. 2c and Fig. 2d, but is not limited thereto. For example, as shown in Fig. 2e, the phase difference adjusting layer 130 may be formed on one surface of the protective layer 120, and the polarizer 110, the protective layer 120, and the phase difference adjusting layer 130 may be sequentially stacked.
[0066] The retardation adjusting layer 130 may be a polymer stretched film obtained by stretching a polymer film capable of imparting optical anisotropy by stretching in an appropriate manner, or a liquid crystal polymer film.
[0067] In one embodiment, the polymer stretched film may be a polymer layer including polyolefins such as polyethylene (PE) or polypropylene (PP), cyclo olefin polymers (COP) such as polynorbornene, polyesters such as polyvinyl chloride (PVC), polyacrylonitrile (PAN), polysulfone (PSU), acrylic resins, polycarbonate (PC), polyethylene terephthalate (PET), polyacrylate, cellulose ester polymers such as polyvinyl alcohol (PVA) or triacetyl cellulose (TAC), or copolymers of two or more monomers among the monomers forming the polymers.
[0068] The method for obtaining the polymer stretched film is not particularly limited, and for example, the polymer material is molded into a film form and then stretched. The method for forming into the film form is not particularly limited, and the film can be molded into a film by known methods such as injection molding, sheet molding, blow molding, injection blow molding, inflation molding, extrusion molding, foam molding, and cast molding, and secondary processing molding methods such as compressed air molding and vacuum molding can also be used. Among them, extrusion molding and cast molding are preferably used. At this time, for example, an unstretched film can be extruded using an extruder equipped with a T-die, a circular die, or the like. When obtaining a molded product by extrusion molding, if a material in which various resin components, additives, etc. are melt-kneaded in advance can be used, it can also be molded through melt kneading during extrusion molding. In addition, various resin components can be dissolved using a solvent common to various resin components, such as chloroform, methylene dichloride, etc., and then cast-dried and solidified to cast-mold an unstretched film.
[0069] The polymer stretched film can be produced by uniaxially stretching the formed film in the mechanical direction (MD; mechanical direction, lengthwise or longitudinal direction) or uniaxially stretching the formed film in the transverse direction (TD; transverse direction, widthwise or transverse direction) of the mechanical direction. Alternatively, a biaxially stretched film can be produced by stretching the formed film using a sequential biaxial stretching method of roll stretching and tenter stretching, a simultaneous biaxial stretching method using tenter stretching, a biaxial stretching method using tubular stretching, or the like.
[0070] The liquid crystal polymer film may include a reactive liquid crystal compound in a polymerized state. The reactive liquid crystal compound may be the same as that of the coating type polarizer.
[0071] In one or more embodiments, the thickness of the retardation adjusting layer 130 may be 10 μm to 100 μm in the case of a polymer stretched film, and 0.1 μm to 5 μm in the case of a liquid crystal polymer film.
[0072] The refractive index adjustment layer 140 is provided to compensate for the refractive index difference of the optical laminate caused by the transparent conductive layer 200, and may serve to improve visibility by reducing the refractive index difference. The refractive index adjustment layer 140 may also be provided to correct a color caused by the transparent conductive layer 200. Meanwhile, when the transparent conductive layer has a pattern, the refractive index adjustment layer 140 can compensate for a transmittance difference between a patterned region where the pattern is formed and a non-patterned region where the pattern is not formed.
[0073] Specifically, the transparent conductive layer 200 is stacked adjacent to another member (e.g., the polarizer 110, etc.) having a different refractive index from the transparent conductive layer 200, and a difference in light transmittance may be induced due to the difference in refractive index between the adjacent layers, and in particular, when a pattern is formed on the transparent conductive layer, a problem may occur in that the patterned region and the non-patterned region are visually distinguishable. Therefore, by including the refractive index control layer 140, the refractive index is compensated to reduce the difference in light transmittance of the optical laminate, and in particular, when a pattern is formed on the transparent conductive layer, the patterned region and the non-patterned region are visually distinguishable from each other.
[0074] In one embodiment, the refractive index of the refractive index adjusting layer 140 may be appropriately selected according to the material of the adjacent other member, and may be preferably 1.4 to 2.6, and more preferably 1.4 to 2.4. In this case, light loss due to a sharp refractive index difference between the transparent conductive layer 200 and other members such as the polarizer 110 can be prevented.
[0075] The refractive index adjustment layer 140 is not particularly limited as long as it can prevent a sharp refractive index difference between other components such as the polarizer 110 and the transparent conductive layer 200, and may be formed using a compound used to form a conventional or later developed refractive index adjustment layer, for example, from a refractive index adjustment layer forming composition containing a polymerizable isocyanurate compound.
[0076] In one embodiment, the polarizing plate 100 may further include other functional layers in addition to the above-mentioned functional layers to supplement or enhance the properties of the polarizer, for example, an overcoat layer to further improve mechanical durability.
[0077] In one or more embodiments, the polarizing plate 100 may have a thickness of 30 to 200 μm, preferably 30 to 170 μm, and more preferably 50 to 150 μm, in which case the polarizing plate 100 maintains its optical properties and allows the manufacture of a thin optical laminate.
[0078] The transparent conductive layer 200 is provided for driving the liquid crystal layer 300, and may be formed in direct contact with the polarizer 100. For example, as shown in Fig. 1, the first transparent conductive layer 200-1 and the second transparent conductive layer 200-2 may be formed in direct contact with the first polarizer 100-1 and the second polarizer 100-2, respectively.
[0079] Conventional optical laminates used in the manufacture of smart windows, etc., are manufactured by forming a conductive layer for driving liquid crystal on one side of a substrate and bonding the other side of the substrate with a polarizing plate. However, the variable transmittance optical laminate according to the present invention is characterized in that it does not include a separate substrate for forming a conductive layer, but directly forms a conductive layer on one side of a polarizing plate, thereby reducing the thickness of the laminate and improving the transmittance and bending characteristics in a light transmission mode.
[0080] In one embodiment, the transparent conductive layer 200 may be formed by direct deposition on one surface of the polarizer 100. In this case, the transparent conductive layer 200 may be formed by directly contacting the pre-treated surface of the polarizer 100 after performing a pre-treatment such as a corona treatment or a plasma treatment on one surface of the polarizer 100 in order to improve adhesion to the polarizer 100. The pre-treatment is not limited to a corona treatment or a plasma treatment, and any conventional or later developed pre-treatment process may be used within a range that does not impair the object of the present invention.
[0081] In another embodiment, the transparent conductive layer 200 may be formed in direct contact with the polarizer 100 via an easy-adhesion layer (not shown) provided on one side of the polarizer 100 in order to improve adhesion to the polarizer 100.
[0082] The transparent conductive layer 200 preferably has a visible light transmittance of 50% or more, and may include, for example, one or more selected from the group consisting of transparent conductive oxides, metals, carbon-based materials, conductive polymers, conductive inks, and nanowires, but is not limited thereto, and conventional or later developed transparent conductive layer materials may be used.
[0083] In one or more embodiments, the transparent conductive oxide may include one or more selected from the group consisting of indium tin oxide (ITO), indium zinc oxide (IZO), indium zinc tin oxide (IZTO), aluminum zinc oxide (AZO), gallium zinc oxide (GZO), fluorine tin oxide (FTO), zinc oxide (ZnO), etc. The metal may include one or more selected from the group consisting of gold (Au), silver (Ag), copper (Cu), aluminum (Al), platinum (Pt), palladium (Pd), chromium (Cr), titanium (Ti), tungsten (W), niobium (Nb), tantalum (Ta), vanadium (V), iron (Fe), manganese (Mn), cobalt (Co), nickel (Ni), zinc (Zn), and alloys containing at least one of them, for example, a silver-palladium-copper (APC) alloy or a copper-calcium (CuCa) alloy. The carbon-based material may include one or more selected from the group consisting of carbon nanotubes (CNTs) and graphene. The conductive polymer may include one or more selected from the group consisting of polypyrrole, polythiophene, polyacetylene, PEDOT, polyaniline, etc. The conductive ink may be an ink in which a metal powder and a curable polymer binder are mixed, and the nanowire may be, for example, a silver nanowire (AgNW).
[0084] The transparent conductive layer 200 may also be formed into a two-layer structure by combining the above materials, for example, into a two-layer structure including a metal layer and a transparent conductive oxide layer to reduce the reflectance and increase the transmittance of incident light.
[0085] The transparent conductive layer 200 may be formed by a method commonly used in the art, for example, a coating process such as spin coating, roller coating, bar coating, dip coating, gravure coating, curtain coating, die coating, spray coating, doctor coating, kneader coating, etc.; a printing process such as screen printing, spray printing, inkjet printing, relief printing, intaglio printing, lithographic printing, etc.; and a deposition process such as CVD (chemical vapor deposition), PVD (physical vapor deposition), PECVD (plasma enhanced chemical vapor deposition), etc.
[0086] The liquid crystal layer 300 can change the driving mode of the optical stack by controlling the transmittance of light incident from one or more directions by an electric field.
[0087] The liquid crystal layer 300 may contain a liquid crystal compound and may be provided, for example, between a first polarizer 100-1 and a second polarizer 100-2 in a light control region, and may be located within a space provided by a sealant 500 and a spacer (not shown) formed along the outer periphery of the liquid crystal layer 300 to seal the liquid crystal layer 300.
[0088] The liquid crystal compound is not particularly limited as long as it is driven by an electric field and can control the light transmittance, and any conventional or later developed liquid crystal compound can be used. For example, the contents regarding the reactive liquid crystal compound of the coating type polarizer described above can be similarly applied.
[0089] The liquid crystal behavior mode of the liquid crystal layer 300 is not particularly limited, and for example, a twisted nematic (TN) mode, a super twisted nematic (STN) mode, a vertical alignment (VA) mode, etc. may be used.
[0090] The alignment film 400 is not particularly limited as long as it is capable of imparting alignment to the liquid crystal compound. For example, the alignment film 400 may be manufactured by applying and curing an alignment film coating composition including an alignment polymer, a photopolymerization initiator, and a solvent. The alignment polymer is not particularly limited, and may be a polyacrylate resin, a polyamic acid resin, a polyimide resin, a polymer including a cinnamate group, or a conventional or later developed polymer capable of exhibiting alignment.
[0091] The sealant 500 may include a curable resin as a base resin. The base resin may be a UV-curable resin or a thermosetting resin known in the art to be used for sealants. The UV-curable resin may be a polymer of a UV-curable monomer. The thermosetting resin may be a polymer of a thermosetting monomer.
[0092] The base resin of the sealant 500 may be, for example, an acrylate-based resin, an epoxy-based resin, a urethane-based resin, a phenol-based resin, or a mixture of the above resins. In one embodiment, the base resin may be an acrylate-based resin, and the acrylate-based resin may be a polymer of an acrylic monomer. The acrylic monomer may be, for example, a multifunctional acrylate. In another embodiment, the sealant 500 may further include a monomer component in the base resin. The monomer component may be, for example, a monofunctional acrylate. In this specification, a monofunctional acrylate may mean a compound having one acrylic group, and a multifunctional acrylate may mean a compound having two or more acrylic groups. The curable resin may be cured by irradiation with ultraviolet light and / or heating. The ultraviolet irradiation conditions or heating conditions may be appropriately performed within a range that does not impair the purpose of the present application. The sealant 500 may further include an initiator, for example, a photoinitiator or a thermal initiator, if necessary.
[0093] The sealant 500 may be formed by a method commonly used in the art, for example, by drawing a sealant-forming composition onto the outer periphery (i.e., non-active area) of the liquid crystal layer 300 using a dispenser equipped with a nozzle.
[0094] In one embodiment, the sealant 500 may have at least a portion where the alignment film 400 is not formed.
[0095] In one embodiment, as shown in FIG. 3, the sealant 500 is formed in a first region A on the alignment film 400. 1 3. A second region A is not formed on the alignment film 400, for example, formed on the transparent conductive layer 200 as shown in FIG. 2 In this case, there may be advantages in terms of improving the active area of the optical stack and improving adhesion between the sealant and the interface.
[0096] In one embodiment, the width of the first region may be 5% to 70% of the sum of the widths of the first region and the second region, more preferably 50% or less, which may further improve adhesion between the active region of the optical stack and the sealant and interface.
[0097] The width of the first region and the width of the second region will be described below.
[0098] Specifically, referring to FIG. 4, the variable transmittance optical laminate according to FIG. 3 has the following characteristics in the planar direction: (i) an alignment film boundary B AL (ii) the alignment film 400 in the region surrounded by the first sealant boundary B SL1 and second sealant boundary B SL2 and the sealant 500 in the area surrounded by the sealant 500.
[0099] As a result, the alignment film 400 and the sealant 500 are overlapped in the planar direction in the region A 1 is the first region A 1and the non-overlapping area A 2 is the second region A 2 It may correspond to:
[0100] At this time, the width W of the first region 1 is the first sealant boundary B SL1 and alignment film boundary B AL The width of the second region W can be defined as the distance between 2 is the alignment film boundary B AL and second sealant boundary B SL2 It can be defined as the distance between
[0101] In one embodiment, the width W of the first region 1 may be from 0.1 mm to 3.0 mm, which may further improve adhesion between the active area of the optical stack and the sealant and interface.
[0102] In one embodiment, a first region A formed between the first alignment film 400-1 and the sealant 500 1 and a first region A formed between the second alignment film 400-2 and the sealant 500. 1 The widths of the first region formed between the first alignment film and the sealant and the first region formed between the second alignment film and the sealant may be substantially the same, but are not necessarily limited thereto. For example, the widths of the first region formed between the first alignment film and the sealant and the first region formed between the second alignment film and the sealant may be different from each other, and in this case, the width of the first region as referred to in the present invention may refer to the larger value of the width of the first region formed between the first alignment film and the sealant and the width of the first region formed between the second alignment film and the sealant.
[0103] The spacer may include at least one of a ball spacer and a column spacer, and is preferably a ball spacer. The number of ball spacers may be one or more, and the ball spacer preferably has a diameter of 1 to 10 μm. In addition, when viewed in a planar direction, the area of the ball spacer in the liquid crystal layer 300 is preferably 0.01 to 10% of the area of the liquid crystal layer 300 in terms of improving the user's visibility and the transmittance in the light-transmitting mode.
[0104] The variable transmittance optical laminate of the present invention may further include other components within the scope of the present invention, for example, may further include an adhesive layer 600 (see FIG. 5), may further include an ultraviolet absorbing layer, a hard coating layer, etc.
[0105] The adhesive layer 600 may be formed using an adhesive or pressure-sensitive adhesive, and preferably has an appropriate adhesive strength so as to prevent peeling, air bubbles, etc. from occurring when the optical laminate is handled, as well as transparency and thermal stability.
[0106] The adhesive may be any conventional or later developed adhesive, for example a light curable adhesive.
[0107] The photocurable adhesive exhibits strong adhesive strength by being crosslinked and cured when exposed to active energy rays such as ultraviolet (UV) rays and electron beams (EB), and may be composed of reactive oligomers, reactive monomers, photopolymerization initiators, etc.
[0108] The reactive oligomer is an important component that determines the properties of the adhesive, and forms a polymer bond by photopolymerization to form a hardened coating. Usable reactive oligomers include polyester resins, polyether resins, polyurethane resins, epoxy resins, polyacrylic resins, silicone resins, etc.
[0109] The reactive monomer functions as a crosslinking agent and a diluent for the reactive oligomer, and affects the adhesive properties. Usable reactive monomers include monofunctional monomers, polyfunctional monomers, epoxy monomers, vinyl ethers, cyclic ethers, and the like.
[0110] The photopolymerization initiator absorbs light energy to generate radicals or cations to initiate photopolymerization, and may be selected from those suitable for the photopolymerizable resin.
[0111] The adhesive may be a conventional or later developed adhesive, and in one or more embodiments, may be an acrylic adhesive, a rubber adhesive, a silicone adhesive, a urethane adhesive, a polyvinyl alcohol adhesive, a polyvinylpyrrolidone adhesive, a polyacrylamide adhesive, a cellulose adhesive, a vinyl alkyl ether adhesive, etc. The adhesive is not particularly limited as long as it has adhesive strength and viscoelasticity, but in terms of availability, etc., it may be preferably an acrylic adhesive, and may contain, for example, a (meth)acrylate copolymer, a crosslinking agent, and a solvent.
[0112] The crosslinking agent may be a conventional or later developed crosslinking agent, and may include, for example, a polyisocyanate compound, an epoxy resin, a melamine resin, a urea resin, a dialdehyde, a methylol polymer, or the like, and preferably includes a polyisocyanate compound.
[0113] The solvent may include a typical solvent used in the field of resin compositions, such as alcohol compounds such as methanol, ethanol, isopropanol, butanol, and propylene glycol methoxy alcohol; ketone compounds such as methyl ethyl ketone, methyl butyl ketone, methyl isobutyl ketone, diethyl ketone, and dipropyl ketone; acetate compounds such as methyl acetate, ethyl acetate, butyl acetate, and propylene glycol methoxy acetate; cellosolve compounds such as methyl cellosolve, ethyl cellosolve, and propyl cellosolve; and hydrocarbon compounds such as hexane, heptane, benzene, toluene, and xylene. These may be used alone or in combination of two or more.
[0114] The thickness of the adhesive layer 600 may be appropriately determined depending on the type of resin acting as an adhesive, adhesive strength, the environment in which the adhesive is used, etc. In one embodiment, the adhesive layer may have a thickness of 0.01 to 50 μm, preferably 0.05 to 20 μm, and more preferably 0.1 to 10 μm, in order to ensure sufficient adhesive strength and minimize the thickness of the optical laminate.
[0115] The ultraviolet absorbing resin is not particularly limited as long as it is capable of preventing deterioration of the optical laminate due to ultraviolet rays. For example, it is possible to use a salicylic acid-based ultraviolet absorbing agent (phenyl salicylate, p-tert-butyl salicylate, etc.), a benzophenone-based ultraviolet absorbing agent (2,4-dihydroxybenzophenone, 2,2'-dihydroxy-4,4'-dimethoxybenzophenone, etc.), a benzotriazole-based ultraviolet absorbing agent (2-(2'-hydroxy-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-t 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)benzotriazole, 2-(2'-hydroxy-3',5'-di-tert-butylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(3'',4'',5'',6''-tetrahydrophthalimidomethyl)-5'-methylphenyl)benzotriazole, 2,2-methylenebis(4-(1,1,3,3-tetramethylbutyl)-6-(2H-benzotriazo 2-(2'-hydroxy-3'-tert-butyl-5'-methylphenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-tert-butyl-5'-(2-octyloxycarbonylethyl)-phenyl)-5-chlorobenzotriazole, 2-(2'-hydroxy-3'-(1-methyl-1-phenylethyl)-5'-(1,1,3,3-tetramethylbutyl)-phenyl)benzotriazole, 2-(2H-benzotriazol-2-yl)-6-(linear and side chain dodecyl)-4-methylphenol, a mixture of octyl-3-[3-tert-butyl-4-hydroxy-5-(chloro-2H-benzotriazol-2-yl)phenyl]propionate and 2-ethylhexyl-3-[3-tert-butyl-4-hydroxy-5-(5-chloro-2H-benzotriazol-2-yl)phenyl]propionate, etc.), cyanoacrylate-based ultraviolet absorbers (2'-ethylhexyl-2-cyano-3,3-diphenylacrylate, ethyl-2-cyano-3-(3',4'-methylenedioxyphenyl)-acrylate, triazine-based ultraviolet absorbers, etc. may be used, and benzotriazole-based ultraviolet absorbers and triazine-based ultraviolet absorbers, which are highly transparent and have an excellent effect of preventing deterioration of the polarizing plate and the transmittance variable layer, are preferred, and benzotriazole-based ultraviolet absorbers with a more suitable spectral absorption spectrum are particularly preferred. The benzotriazole-based ultraviolet absorbers may be bis(Bis)-modified, for example, 6,6'-methylenebis(2-(2H-benzo[d][1,2,3]triazol-2-yl)-4-(2,4,4-trimethylpentan-2-yl)phenol), 6,6'-methylenebis(2-(2H-benzo[d][1,2,3]triazol-2-yl)-4-(2-hydroxyethyl)phenol), etc.,
[0116] The hard coating layer is not particularly limited as long as it is for protecting components such as a polarizing plate and a transmittance variable layer from external physical and chemical impacts, and any conventional or later developed hard coating layer may be used.
[0117] In one embodiment, the hard coating layer may be formed by applying a composition for forming a hard coating layer onto another member and then curing the composition with light or heat. The composition for forming a hard coating layer is not particularly limited and may include, for example, a photocurable compound and a photoinitiator.
[0118] The photocurable compound and photoinitiator may be any compound commonly used in the art without any limitation. For example, the photocurable compound may be a photopolymerizable monomer, a photopolymerizable oligomer, etc., and examples of the photocurable compound include monofunctional and / or polyfunctional (meth)acrylates, and examples of the photoinitiator include oxime esters, etc.
[0119] The present invention includes the variable transmittance optical laminate, as well as a smart window including the same. The present invention also includes an automobile in which the smart window is applied to at least one of a front window, a rear window, a side window, a sunroof window, and an interior partition, and a building fixture including the smart window. EXAMPLES
[0120] Hereinafter, the present invention will be described in detail with reference to the embodiments. However, the present invention is not limited to the embodiments disclosed below, and may be embodied in various different forms. However, the embodiments are provided to fully disclose the present invention and to fully inform those skilled in the art of the present invention of the scope of the invention, and the present invention is defined only by the scope of the claims.
[0121] Examples and Comparative Examples: Production of Optical Laminates Variable transmittance optical laminates of the examples and comparative examples having a laminate structure of a first laminate [first polarizer / first transparent conductive layer / first alignment film] / liquid crystal layer (including sealant) / second laminate (second alignment film / second transparent conductive layer / second polarizer) were manufactured according to the width of the first region shown in Table 1. The sealant was formed with a width of 4 mm using sealant UVF006 (Sekisui Co., Ltd.) through a sealant dispenser equipped with SHOT mino 200Sx (Musashi Co., Ltd.).
[0122] In this case, the width of the first region is shown with the sum of the width of the first region and the width of the second region being 100%.
[0123] [Table 1]
[0124] Experimental example (1): Evaluation of sealant peeling force The sealant peel strength was measured using a tensile test evaluation device AG-X 1kN (manufactured by SHIMAZDU Co., Ltd.).
[0125] Specifically, the optical laminates according to the examples and comparative examples were cut to have a width of 25 mm and an overall length of 150 mm to prepare test pieces.
[0126] Thereafter, the first laminate of test pieces was fixed on top of the upper and lower jigs of the tensile test evaluation device, and the second laminate was fixed on the bottom.
[0127] Thereafter, the sealant was peeled at a speed of 300 mm / min using a 180° peel method, and the average peel strength of the sealant peeled section of 30 to 120 mm was measured. The evaluation results are shown in Table 2 below.
[0128] Experimental example (2): Evaluation of cross transmittance The cross transmittance (%) was measured using a spectrophotometer (CM-3700d, manufactured by Konica Minolta).
[0129] Specifically, the sealant line of the optical laminates according to the examples and comparative examples was positioned at the center of the sensor, and the measurement area was adjusted to be within the liquid crystal layer active region range of the sealant boundary line, after which the cross transmittance was measured, and the evaluation results are shown in Table 2 below.
[0130] [Table 2]
[0131] Referring to Table 2, the optical laminates of Examples 1 to 4, in which the ratio of the width of the first region to the sum of the widths of the first region and the second region is 5% to 70%, not only have a good sealant peel strength of 102 to 451 mN / 4 mm, but also have a cross transmittance of the active region of the liquid crystal layer adjacent to the sealant boundary (i.e., the cross transmittance of the active region measured at the interface between the active region of the liquid crystal layer and the first region) of 0% or 0.1%, or essentially 0%.
[0132] On the other hand, the optical laminate of Comparative Example 1, in which the ratio of the width of the first region to the sum of the widths of the first and second regions is 0% (i.e., there is essentially no overlapping area between the alignment film and the sealant), has a cross transmittance of the active region of the liquid crystal layer adjacent to the sealant boundary (i.e., the cross transmittance of the active region measured at the interface between the active region of the liquid crystal layer and the first region) of 3.0%, indicating that some side light leakage occurred compared to Examples 1 to 4.
[0133] In addition, the optical laminate of Comparative Example 2, in which the ratio of the width of the first region to the sum of the width of the first region and the width of the second region is 100% (i.e., the sealant is formed on the alignment film), had a sealant peel strength of 89 mN / 4 mm, indicating that the interfacial adhesion of the sealant was reduced compared to Examples 1 to 4.
[0134] Therefore, the optical laminate of the present invention has a sealant peel strength of 100 mN / 4 mm or more, preferably 100 mN / 4 mm to 500 mN / 4 mm, and a cross transmittance of the active region of the liquid crystal layer adjacent to the sealant boundary (i.e., the cross transmittance of the active region measured at the interface between the active region of the liquid crystal layer and the first region) of 0% or more and less than 3.0%, preferably 0% or substantially 0%, and it can be seen that the interfacial adhesion between the active region of the liquid crystal layer and the sealant is further improved compared to conventional optical laminates.
[0135] Meanwhile, the cross transmittance being "substantially 0%" is not limited to the case where the cross transmittance is completely 0%, but may also include a range where the cross transmittance exceeds 0% and is within the range of measurement error and can be regarded as being almost 0% (for example, a cross transmittance of 0.1% or less). [Industrial Applicability]
[0136] According to the variable transmittance optical laminate of the present invention, it is possible to omit the steps of forming a conductive layer on a substrate and then bonding this to other components in order to form a conventional optical laminate, thereby simplifying the manufacturing process compared to conventional optical laminates.
Claims
1. a first laminate including a first polarizing plate, a first transparent conductive layer, and a first alignment film laminated in this order; a second laminate facing the first laminate and including a second polarizing plate, a second transparent conductive layer, and a second alignment film laminated in this order; a liquid crystal layer disposed between the first stack and the second stack; a sealant formed along an outer periphery of the liquid crystal layer to seal the liquid crystal layer, At least one of the first transparent conductive layer and the second transparent conductive layer is formed in direct contact with one of the first polarizing plate and the second polarizing plate, the sealant includes a first region overlapping at least one of the first alignment film and the second alignment film in a planar direction and a second region not overlapping the first alignment film and the second alignment film, A variable transmittance optical stack, wherein the width of the first region is 5% to 70% of the sum of the width of the first region and the width of the second region.
2. the sealant region corresponding to the first region is a sealant region formed on at least one of the first alignment film and the second alignment film, The variable transmittance optical laminate according to claim 1 , wherein the sealant region corresponding to the second region is a sealant region that is not formed on the first alignment film and the second alignment film.
3. The variable transmittance optical stack of claim 1 , wherein the sum of the width of the first region and the width of the second region is a sealant width.
4. The variable transmittance optical stack of claim 1 , wherein the width of the first region is from 0.1 mm to 3.0 mm.
5. 2. The variable transmittance optical stack of claim 1, wherein the crossed transmittance of the active region measured at the interface between the active region and the first region of the liquid crystal layer is greater than or equal to 0% and less than 3.0%.
6. 2. The variable transmittance optical stack of claim 1, wherein the peel strength of the sealant is from 100 mN / 4 mm to 500 mN / 4 mm.
7. 2. The variable transmittance optical laminate of claim 1, wherein at least one of the first transparent conductive layer and the second transparent conductive layer is formed in direct contact with one of the first polarizer and the second polarizer without a separate substrate between the transparent conductive layer and the first polarizer and the second polarizer.
8. The variable transmittance optical laminate of claim 1 , wherein at least one of the first transparent conductive layer and the second transparent conductive layer includes an easy-adhesion layer between the first polarizing plate and the second polarizing plate and is formed in direct contact with the first polarizing plate and the second polarizing plate.
9. 2. The variable transmittance optical laminate of claim 1, wherein at least one of the first transparent conductive layer and the second transparent conductive layer comprises at least one selected from the group consisting of transparent conductive oxides, metals, carbon-based materials, conductive polymers, conductive inks, and nanowires.
10. 2. The variable transmittance optical laminate according to claim 1, wherein at least one of the first polarizing plate and the second polarizing plate includes one or more functional layers selected from the group consisting of a protective layer, a phase difference adjusting layer, and a refractive index adjusting layer.
11. The variable transmittance optical laminate according to claim 1 , wherein at least one of the first polarizing plate and the second polarizing plate has a thickness of 30 to 200 μm.
12. The variable transmittance optical laminate according to claim 1 , wherein the liquid crystal layer comprises at least one selected from the group consisting of a ball spacer and a column spacer.
13. The variable transmittance optical stack of claim 12, wherein the ball spacer has a diameter of 1 to 10 μm.
14. The variable transmittance optical laminate according to claim 12, wherein the area of the ball spacer in the liquid crystal layer is 0.01% to 10% of the area of the liquid crystal layer.
15. The variable transmittance optical laminate according to claim 1 , further comprising at least one layer selected from the group consisting of an alignment film, an adhesive layer, an ultraviolet absorbing layer, and a hard coating layer.
16. A method for producing the variable transmittance optical laminate according to claim 1 .
17. A smart window comprising the variable transmittance optical stack according to any one of claims 1 to 15.
18. 20. A car comprising the smart window according to claim 17 applied to at least one of a front window, a rear window, a side window, a sunroof window, and an interior partition.
19. 20. A building fixture comprising the smart window of claim 17.